Head excursion in frontal impacts is lower in high back booster seats than in forward facing child seats with internal harnesses designed for children up to 8 years of age. (4th July 2022) - Bilston, Lynne E.; Mills, Elizabeth; Kent, Nicholas; Brown, Julie; Whyte, Tom
Abstract: Objective: It is often assumed that a child restraint with a five or six-point internal harness provides greater protection for children in frontal crashes than a booster seat with a lap-sash seat belt. However, most research comparing these restraint types has focused on protection for children aged up to approximately 3–4 years of age. Recently, harnessed child restraints for older children up to approximately 8 years of age have become available, but there is little data on their performance compared to booster seats for children over 4 years of age. This study aimed to compare frontal crash performance of a series of harnessed child restraints for children aged 4–8 years to booster seats. Methods: Four large harnessed child restraints (Type G in the Australian Standard, AS/NZS 1754:2013) and six high back booster seats (Type E in AS/NZS 1754:2013) were tested in frontal impact on a deceleration sled. Head and pelvis accelerations were recorded and head excursions were measured from high speed video. Results: Head excursion was an average of 92 mm greater in the large harnessed child restraints than the high back booster seats. The initial position of the head in Type G restraints, an average of 58 mm further forward compared to Type E boosters, was the main contributor to the larger head excursion during impact. Conversely, peak head accelerations in the impact phase were, on average, 37.2 g lower in the large harnessed child restraints than the high back booster seats. Conclusions: These data suggest that recommendations for harnessed restraints and booster seats for children aged 4–8 years is not as obvious as is sometimes assumed. Harnessed restraints allow greater head excursion in frontal impacts, potentially increasing the chances of head impacts, especially in vehicles with limited clearance between the restraint and the seat in front. The likelihood, and types of, incorrect use that occur in each restraint type, the vehicle occupant space, and the restraint's crash performance under ideal conditions should be considered in recommending restraints for these older children.